Fall Armyworm: Impacts and Implications for Africa. (1st October 2017) - Day, Roger; Abrahams, Phil; Bateman, Melanie; Beale, Tim; Clottey, Victor; Cock, Matthew; Colmenarez, Yelitza; Corniani, Natalia; Early, Regan; Godwin, Julien; Gomez, Jose; Moreno, Pablo Gonzalez; et al.
The appearance of Fall Armyworm (FAW) (Spodoptera frugiperda) in Africa has caused much consternation: "The hungry caterpillar threatening a global food crisis", according to a headline in the Guardian newspaper. The UK Department for International Development (DFID) commissioned CABI to compile an evidence note, which was published by CABI in September 2017. This article is a summary of the evidence note, which aimed to assess the potential impact of FAW in Africa if left uncontrolled, and recommend and prioritise control options. The first confirmed reports of FAW were from West Africa in early 2016. Research to date suggests that both strains of FAW that are found in the Americas entered Africa, perhaps as stowaways on commercial aircraft, either in cargo containers or airplane holds, before subsequent widespread dispersal by the wind. The probability is high (>90%) that the introduction to Africa was from the characterised Florida strain of FAW, which is restricted to the eastern seaboard of the USA, and the Caribbean islands. Based on information from literature searches, personal communications and internet mining, as for August 2017 28 countries have confirmed the presence of FAW. A further nine countries suspect its presence, or are awaiting official confirmation of the pest in the country. Two countries (Somalia and Djibouti) have conducted surveys and not found any FAW. Using distribution and climate data collected from South America and in Ghana and Zambia, models were used to investigate the environmental (climatic) factors affecting the distribution of FAW. Results from multiple models have been combined to produce an environmental suitability index for FAW across Africa. Fall Armyworm (FAW) in Africa has the potential to cause maize yield losses in a range from 8.3 to 20.6m tonnes per annum, in the absence of any control methods, in just 12 of Africa's maize-producing countries. This represents a range of 21%–53% of the annual production of maize averaged over a three year period in these countries. The value of these potential losses is estimated at between 2, 481m and 6, 187m. FAW should be expected to spread throughout suitable habitats in mainland sub-Saharan Africa within the next few cropping seasons. Northern Africa and Madagascar are also at risk. As of August 2017, the pest has been confirmed present in 28 countries in Africa (compared to 12 in April 2017), with suspected presence in a further 9 countries. Control of FAW requires an integrated pest management (IPM) approach. Immediate recommendations include (i) awareness raising campaigns on FAW symptoms, early detection and control, including beneficial agronomic practices; (ii) national preparation and communication of a list of recommended, regulated pesticides and biopesticides and their appropriate application methods. Work should also start immediately to (i) assess preferred crop varieties for resistance or tolerance to FAW; (ii) introduce classical biological control agents from the Americas. A conducive policy environment should promote lower risk pest management approaches.